DESIGN AND CONSTRUCTION OF A TUNEL DRYER FOR FOOD CROPS DRYING - J.O. Olajide, A.S. Ajala, P.O. Ngoddy, (International Multidisciplinary Research Journal)
Conventional sun drying of tropical crops often result in low quality product due to unpredictable nature of weather. Utilizing mechanical dryer such as tunnel dryer can improve the quality of the products as well as increasing the acceptability of such crop in global market. In this study, a tunnel dryer in two modes of operation (co-current and counter-current) with a capacity of 35kg of chips per batch was designed, fabricated and tested. The dryer had a chamber volume of 0.408m3; the number of trucks in the tunnel was 6, each truck contained 6 trays. The operating temperature of the pilot dryer ranged from 50 to 150 oC and air velocity ranged from 2 to 8 m/s, respectively. Cassava chips was used to test the dryer and the results showed that the dryer reduced the moisture content from 75 to 14% in 8 hours with drying constant of 2.42/h.